Answer:
Bhhjjj
Step-by-step explanation:thjkkmnb
Answer:
a = 18
Step-by-step explanation:
a/6 = 3
Multiply each side by 6
a/6*6=3 *6
a = 18
Complete Question:
Convert 3x-y+2=0 in rectangle form to polar form
Answer:
r ( 3cosθ - sinθ) = -2
Step-by-step explanation:
The equation so given is already in rectangular form, the task is to convert it to polar form.
3x - y + 2 = 0
To transform an equation from the rectangular to the polar coordinate:
x = r cosθ
y = r sinθ
Substitute the representations for x and y into the given equation:
3(r cosθ) - (r sinθ) + 2 = 0
3rcosθ - rsinθ = -2
The polar representation of the equation then becomes:
r ( 3cosθ - sinθ) = -2
Answer:
32.66 units
Step-by-step explanation:
We are given that

Point A=(-2,-4) and point B=(1,20)
Differentiate w.r. t x

We know that length of curve

We have a=-2 and b=1
Using the formula
Length of curve=
Using substitution method
Substitute t=12x+14
Differentiate w.r t. x


Length of curve=
We know that

By using the formula
Length of curve=![s=\frac{1}{12}[\frac{t}{2}\sqrt{1+t^2}+\frac{1}{2}ln(t+\sqrt{1+t^2})]^{1}_{-2}](https://tex.z-dn.net/?f=s%3D%5Cfrac%7B1%7D%7B12%7D%5B%5Cfrac%7Bt%7D%7B2%7D%5Csqrt%7B1%2Bt%5E2%7D%2B%5Cfrac%7B1%7D%7B2%7Dln%28t%2B%5Csqrt%7B1%2Bt%5E2%7D%29%5D%5E%7B1%7D_%7B-2%7D)
Length of curve=![s=\frac{1}{12}[\frac{12x+14}{2}\sqrt{1+(12x+14)^2}+\frac{1}{2}ln(12x+14+\sqrt{1+(12x+14)^2})]^{1}_{-2}](https://tex.z-dn.net/?f=s%3D%5Cfrac%7B1%7D%7B12%7D%5B%5Cfrac%7B12x%2B14%7D%7B2%7D%5Csqrt%7B1%2B%2812x%2B14%29%5E2%7D%2B%5Cfrac%7B1%7D%7B2%7Dln%2812x%2B14%2B%5Csqrt%7B1%2B%2812x%2B14%29%5E2%7D%29%5D%5E%7B1%7D_%7B-2%7D)
Length of curve=
Length of curve=
Length of curve=